Analisis Pertahanan Diri Tokoh Utama dalam Novel Lembata Karya F.Rahardi - Anggitha Sahari; Candra Rahma Wijaya Putra (Jurnal Semantik, 2024)
The objectives of this study are 1) to identify the form of self-defense of the main character in the novel Lembata by F.Rahardi 2) to identify the conflict experienced by the main character in the novel. This research uses a qualitative descriptive method. The research approach uses literary psychology theory related to self-defense mechanisms proposed by Sigmund Freud. The research data is in the form of story excerpts, sentences, paragraphs, or dialogues that show a form of self-defense. The research data source is the Lembata Novel by F.Rahardi. The results of this study found that there are several forms of self-defense in the Lembata novel as follows, 8 forms of repression, 4 forms of rationalization, 1 form of diversion, and 1 form of sublimation self-defense. Another data analysis found the existence of internal conflicts indicated that the character did not dare to break his vow, feelings of guilt from the character, the character's inner conflict with God, feelings of doubt or indecision, and the condition of loss felt by the character. The character's external conflict is found in the form of conflict between one character and another.